Modeling of the spread of motor transport noise in Šiauliai city - Paulauskas, Leonas; Klimas, Robertas (Journal of Environmental Engineering and Landscape Management, 2011)
Rapidly growing urbanization causes the increase of noise level of various sources, that have a negative impact upon people's health. The contribution of noise caused by motor transport in city environment composes up to 80% of general impact of all the sources. The article presents the results of modeling of the spread of motor transport noise of Šiauliai city, maps of motor transport noise, recommendations for management of environment noise. MapNoise programme module, adapted to work in the ArcGIS Desktop 9.1 environment, was used for modeling motor transport noise. Noise measurement researches have been carried out using digital noise isolator Nor121, completed with digital level detector. NorXfar software was used to send the data to personal computer. Having evaluated the validity of modeling results it has been determined that the difference between the night noise modeling and measurement results does not exceed 2.2%, and varies from 0.5dB(A) to 1.1 dB(A). The obtained results indicate that 7.2% of the apartments of all city residents are influenced by the LDEN noise that exceeds the permitted noise level (LDEN >65 dB(A)) and 31.2% of the apartments of the residents are influenced by night noise that exceeds the permitted noise level (LN > 55 dB(A)).Article in English.Autotransporto triukšmo sklaidos Šiauliuose modeliavimas Santrauka. Sparčiai vykstant urbanizacijos procesui, kinta įvairių šaltinių keliamo triukšmo lygis, didėja neigiama įtaka žmonių sveikatai. Miestų aplinkoje iki 80 % visuminio visų triukšmo šaltinių poveikio tenka autotransporto keliamam triukšmui.Straipsnyje pateikta autotransporto triukšmo sklaidos Šiauliuose modeliavimo rezultatai, autotransporto triukšmo žemėlapiai, aplinkos triukšmo valdymo rekomendacijos. Autotransporto triukšmui modeliuoti naudotas MapNoise programinismodulis, pritaikytas darbui ArcGIS Desktop 9.1 aplinkoje. Iš rezultatų matyti, kad 7,2% visų miesto gyventojų būstų yra veikiami paros triukšmo, viršijančio leidžiamąjį triukšmo lygį (LDVN > 65 dB(A)), ir 31,2% gyventojų būstų veikiami nakties triukšmo, viršijančio leidžiamąjį triukšmo lygį (LN > 55 dB(A)). Įvertinus modeliavimo rezultatų patikimumą nustatyta, kad paros ir nakties triukšmo modeliavimo ir matavimo rezultatų neatitiktis neviršija 2,2 % ir svyruoja nuo 0,5dB(A) iki 1,1dB(A).Reikšminiai žodžiai: triukšmo tyrimai, transporto triukšmas, triukšmo rodikliai, autotransporto triukšmo žemėlapis, triukšmo modeliavimas.Моделирование рассеяния транспортного шума в городе ШяуляйРезюме. При быстром росте урбанизации увеличивается уровень шума, создаваемого разными источниками и отрицательно влияющего на здоровье населения. Шум от автотранспорта в городах составляет около 80% от всех источников шума. В статье представлены результаты моделирования рассеяния шума от автотранспорта в городеШяуляй, карты автотранспортного шума, рекомендации по управлению шумом в окружающей среде. Приизмерении шума был использован числовой анализатор шума № 121, укомплектованный с числовым детекторомуровня RMS. Для передачи данных в персональный компьютер использована программа NorXfer. Для моделирования автотранспортного шума использован программный модуль MapNoise, приспособленный дляработы в среде ArcGIS desktop 9.1. При анализе достоверности результатов моделирования было установлено, чтоих отличие от результатов измерения шума в течение суток и ночное время не превышает 2,2% и колеблется от0,5дБ(A) до 1,1дБ(A). Результаты исследования свидетельствуют о том, что 7,2% жилых помещений городаподвергаются суточному шуму, уровень которого превышает допустимый (LDVN > 65 дБ(A)) и 31,2% жилых помещений города подвергаются шуму в ночное время, уровень которого превышает допустимый (LN > 55дБ(A)).Ключевые слова: исследования шума, автотранспортный шум, показатели шума, карта автотранспортного шума, моделирование шума.